The Effect of Third Party Funds and Assets on Profits at PT. Riau Kepri Syariah Regional Development Bank - Hapsila, Angga; Astarina, Ivalaina; Remofa, Yudha; Supriyadi, Agus (International Journal of Applied Research and Sustainable Sciences, 2024)
The research was conducted to see the effect of tThe research was conducted to see the effect of third party funds and assets on profits at PT. Riau Regional Development Bank Kepri Syariah. The data in this study used secondary data from 2009 to 202, through a quantitative approach. Researchers utilize SPSS version 24 in managing data. The results showed that third-party funds partially had no effect on profits and assets partially affected profits. The results of research on third-party funds and assets simultaneously affect profits. Keywords: Profit, Third Party Funds and Assetshird party funds and assets on profits at PT. Riau Regional Development Bank Kepri Syariah. The data in this study used secondary data from 2009 to 202, through a quantitative approach. Researchers utilize SPSS version 24 in managing data. The results showed that third-party funds partially had no effect on profits and assets partially affected profits. The results of research on third-party funds and assets simultaneously affect profits. Keywords: Profit, Third Party Funds and Assets